Edukasi dalam Pembibitan Sawi Warga di Kelurahan Karanganyar Kota Pasuruan - Alvian Dwisetyawan; Dewi Ainiyah; M. Yanuar Ibra M; Nazila Safira Makkah; Ilmiyatur Rosidah (Jurnal Kemitraan Masyarakat, 2024)
This article explores a sustainable education program in mustard green cultivation implemented through collaboration between local residents and UNIWARA KKN (Community Service Program) students in Kelurahan Karanganyar. The program aims to enhance the knowledge and skills of local residents in sustainable mustard green cultivation techniques, including the use of appropriate growing media, efficient irrigation techniques, and the management of pests and plant diseases without harmful chemicals. The method used in this study is **Community-Based Participatory Research (CBPR)**: working together with local residents and engaging in hands-on field practice to apply proper cultivation techniques. The research shows that this educational program not only successfully improves local residents' knowledge and skills in mustard green cultivation but also strengthens the relationship between the community and academics. Active community participation in this program results in significant positive impacts, including a reduction in the use of synthetic chemicals, increased crop yields, and more environmentally friendly agriculture